Distribution of Inheritance Property Before The Testator Dies: A KHI and Civil Law Perspective in Indonesia - Riski, Rahmat (Literasi Hukum, 2023)
This research examines the practice of distributing inheritance before the testator dies from the perspective of the Compilation of Islamic Laws (KHI) and the civil law that applies in Indonesia. The problem studied in this research is the practice of distributing inheritance before the testator dies and whether such distribution is permitted according to KHI and civil law in Indonesia. This research applied literature review methodology that used a normative approach. The result shows that the practice of distributing inheritance before the testator dies according to KHI and civil law in Indonesia is not permitted, because the death of the testator is an absolute requirement for the distribution of inheritance. However, KHI provides an alternative for heirs to appoint someone as the person who will divide the inheritance after the testator dies. Concerning on civil law in Indonesia, it is stated that the distribution of inheritance while the testator is still alive cannot be carried out as it has no legal force and its status is null and void.